INNOVATIONS IN TECHNOLOGY-BASED LEARNING TO ENHANCE 21ST CENTURY COMPETENCIES - Joko Sugiarto; Widjanarko; Moh. Imron Rosidi (CV. ADIBA AISHA AMIRA, 2024)
Innovations in technology-based learning have become a key focus in the effort to improve 21st century competencies. This research examines the latest technological approaches in education and their impact on the development of critical skills needed in the digital era. The method used includes literature analysis. Results show that the integration of technologies such as artificial intelligence, virtual reality and adaptive learning has great potential in improving learners' problem-solving, creativity, collaboration and digital literacy. However, the research also identified challenges such as the digital divide and the need to improve educators' competencies. In conclusion, technology-based learning innovation requires a holistic and sustainable approach, involving all stakeholders to maximise its potential in preparing a generation ready for the challenges of the 21st century